Actin foci facilitate activation of the phospholipase C-gamma in primary T lymphocytes via the WASP pathway - Kumari, S; Depoil, D; Dustin, M; Martinelli, R; Judokusumo, E; Carmona, G; Gertler, F; Kam, L; Carman, C; Burkhardt, J; Irvine, D (eLife Sciences Publications, 2015)
Wiscott Aldrich Syndrome protein (WASP) deficiency results in defects in calcium ion signaling, cytoskeletal regulation, gene transcription and overall T cell activation. The activation of WASP constitutes a key pathway for actin filament nucleation. Yet, when WASP function is eliminated there is negligible effect on actin polymerization at the immunological synapse, leading to gaps in our understanding of the events connecting WASP and calcium ion signaling. Here, we identify a fraction of total synaptic F-actin selectively generated by WASP in the form of distinct F-actin ‘foci’. These foci are polymerized de novo as a result of the T cell receptor (TCR) proximal tyrosine kinase cascade, and facilitate distal signaling events including PLCγ1 activation and subsequent cytoplasmic calcium ion elevation. We conclude that WASP generates a dynamic F-actin architecture in the context of the immunological synapse, which then amplifies the downstream signals required for an optimal immune response.